Anti-tumorigenic effects of a novel digitoxin derivative on both estrogen receptor–positive and triple-negative breast cancer cells - Yogesh M Kulkarni; Juan S Yakisich; Neelam Azad; Rajkumar Venkatadri; Vivek Kaushik; George O’Doherty; Anand Krishnan V Iyer (Tumor Biology)
While there are targeted treatments for triple positive breast cancers, lack of specific biomarkers for triple-negative breast cancers (TNBC) has hindered the development of therapies for this subset of cancers. In this study, we evaluated the anticancer properties of cardiac glycoside Digitoxin (Dtx) and its synthetic analog MonoD on breast cancer cell lines MCF-7 (estrogen receptor-positive breast cancer) and MDA-MB-468 (triple-negative breast cancer). Both cardiac glycosides, at concentrations within the therapeutic range, increased the fraction of cells in the G 0 /G 1 phase of the cell cycle, decreased viability, and inhibited the migration of MCF-7 and MDA-MB-468 cells. Both cardiac glycosides increased production of superoxide and induced apoptosis in both cell types. Reduced protein levels of nuclear factor kappa B and IkappaB kinase-beta were found in cardiac glycoside-treated cells, indicating that the cellular effects of these compounds are mediated via nuclear factor kappa B pathway. This study demonstrates the cytotoxic potential of digitoxin, and more importantly its synthetic analog MonoD, in the treatment of triple-positive breast cancer and more importantly the aggressive triple-negative breast cancer. Collectively, this study provides a basis for the reevaluation of cardiac glycosides in the treatment of breast cancer and more importantly reveals their potential in the treatment of triple-negative breast cancers.